2000
DOI: 10.1007/s001040070002
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering mit mesenchymalen Stammzellen zur Knorpel- und Knochenneubildung

Abstract: Tissue engineering offers the possibility to fabricate living substitutes for tissues and organs by combining histogenic cells and biocompatible carrier materials. Pluripotent mesenchymal stem cells are isolated and subcultured ex vivo and then their histogenic differentiation is induced by external factors. The fabrication of bone and cartilage constructs, their combinations and gene therapeutic approaches are demonstrated. Advantages and disadvantages of these methods are described by in vitro and in vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…We used additional bone marrow aspirates combined with bone grafting in 3 cases to achieve a maximum of cell potential within the area to be regenerated. Different authors reported on the possible use of progenitor cells from different tissues like bone marrow and periosteum with or without scaffolds for bone and cartilage repair [1,2,7,13,17,28,34]. Although there are no clinical trials with a longer follow up, the high potential of these cellbased strategies is evident.…”
Section: Discussionmentioning
confidence: 99%
“…We used additional bone marrow aspirates combined with bone grafting in 3 cases to achieve a maximum of cell potential within the area to be regenerated. Different authors reported on the possible use of progenitor cells from different tissues like bone marrow and periosteum with or without scaffolds for bone and cartilage repair [1,2,7,13,17,28,34]. Although there are no clinical trials with a longer follow up, the high potential of these cellbased strategies is evident.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrozyten, welche aus hMSC gewonnen werden, dedifferenzieren in vitro zunehmend zu fibroblastischen Zellen. Diese morphologische Veränderung geht mit einem Switch der Kollagensynthese von Typ II zu Typ I einher [68]. Dieses Phänomen ist unter anderem für die gegenwärtig bevorzugte Verwendung von bereits ausdifferenzierten Chondrozyten für die Zelltherapie (autologe Chondrozytentransplantation) mitverantwortlich.…”
Section: B) Dedifferenzierungunclassified
“…Limitations of this approach, however, include 1) high cost and 2) need for repeated applications secondary to the short half-life of the protein. Other experimental therapies include the development of injectable biological bone substitutes as well as exposure of human mesenchymal stem cells to BMP-2 ex vivo , thus, inducing their osteoblastic differentiation [ 7 , 8 ]. Transduction of target cells with a replication-deficient adenovirus, designed to carry cDNA encoding for BMP-2, represents a novel approach for local delivery of BMP-2 to the region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using genetically altered soft tissue flaps as biologic pumps has been demonstrated by Liu et al and Michaels et al in a rat model [ 13 - 15 ]. The present study represents the first attempt of assessing whether muscle flaps can be altered genetically so as to not only provide soft tissue coverage but also enhance osseous healing by local production of growth factors, as muscle tissue is known to possess an ample quantity of mesenchymal stem cells capable of osteoblastic differentiation [ 8 ]. Furthermore, BMP-2 has an angiogenetic potential, which could aid in facilitating the healing process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%